PRESERVICE MATHEMATICS TEACHERS’ REASONING IN SOLVING CRITICAL THINKING PROBLEM - Herizal, Herizal; Marhami, Marhami; Fonna, Mutia; Rohantizani, Rohantizani (PATTIMURA UNIVERSITY, 2022)
Mathematical reasoning is one of the abilities that must have by students after learning mathematics. To improve students’ reasoning, teachers also have to good in reasoning. Due to the importance of reasoning for teachers, a qualitative descriptive research was conducted to analyze how the reasoning of preservice mathematics teachers in solving critical thinking problem. The data were collected through instrument test that consists of one problem about perimeter of a rectangle from 40 preservice mathematics teachers of first year in one of public universities in North Aceh, Aceh, Indonesia. The problem measured the skill of manipulating mathematical process; constructing mathematical proof, and drawing conclusion. Their works were analyzed for each indicator of reasoning. The result showed that more than 75% preservice mathematics teachers were wrong in solving the problem. They were not good in constructing mathematical proof to draw a conclusion. It concludes that preservice mathematics teachers’ ability in mathematical reasoning was not satisfied. The ability still needs to be improved through learning activities and they must be accustomed to the problems or situations that involving reasoning